GABA receptor rho subunit expression in the developing rat brain. - Enz, Ralf; et al. (DEV BRAIN RES, 2005)
Ionotropic GABA C receptors are composed of ρ 1, ρ 2 and ρ 3 subunits. Although the distribution of ρ subunit mRNAs in the adult brain has been studied, information on the developmental regulation of different ρ subunits in the brain is scattered and incomplete. Here, GABA C receptor ρ subunit expression was studied in the developing rat brain. In situ hybridization on postnatal brain slices showed ρ 2 mRNA expression from newborn in superficial gray layer (SGL) of superior colliculus (SuC), and from the first postnatal week in the hippocampal CA1 region and pretectal nucleus of the optic tract. ρ 2 mRNA was also expressed in the adult dorsal lateral geniculate nucleus. Quantitative RT-PCR revealed expression of all three ρ subunits in the hippocampus and superior colliculus from the first postnatal day. In the hippocampus, ρ 2 mRNA expression clearly dominated over ρ 1 and ρ 3, whereas in the superior colliculus, ρ 1 mRNA expression levels were similar to ρ 2. In both areas, a clear up-modulation of ρ 2 and ρ 3 mRNA during the first postnatal week was detected. GABA C receptor protein expression was confirmed in adult hippocampus, superior colliculus and dorsal lateral geniculate nucleus by immunohistochemistry. Our results demonstrate for the first time the expression of all three ρ subunit mRNAs in several regions of the developing and adult rat brain. Our quantitative data allows assessment of putative subunit combinations in the superior colliculus and hippocampus. From the selective distribution of ρ subunits, it may be hypothesized that GABA C receptors are specifically involved in aspects of visual image motion processing in the rat brain. © 2004 Elsevier B.V. All rights reserved.
UnivIS-Import:2017-12-18:Pub.2005.med.IB.profes_1.gabare
Keywords: GABA; Hippocampus; Immunohistochemistry; In situ hybridization; qRT-PCR; Superior colliculus